1978
DOI: 10.1111/j.1432-1033.1978.tb12764.x
|View full text |Cite
|
Sign up to set email alerts
|

Refolding and Reactivation of Escherichia coli Tryptophan Synthase β2 Subunit after Inactivation and Dissociation in Guanidine Hydrochloride at Acidic pH

Abstract: The isolated 82 subunit of Eseherichia c d i tryptophan synthase can be reversibly deactivated and dissociated in the presence of 4.5 M guanidine hydrochloride at pH 2.3. Using gel chromatography and ultracentrjfugation, the denatured state is found to be the homogeneous, inactive monomer (Ail, = 44000, . S~O .~ = 1.7 S). Removal of the denaturant by dilution leads to 90 k 3 ?( regain of specific activity and complete recovery of the enzymatic, hydrodynamic, and spectral properties characterizing the native, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

1979
1979
2006
2006

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 12 publications
3
13
0
Order By: Relevance
“…Based on earlier reactivation experiments with oligomeric enzymes [34-361 it has been shown recently that E. coli tryptophan synthase f l~ subunit can be reversibly denatured in the presence of 2 4 M urea [37] or 4.5 M guanidine . HCl at acidic pH [38]. Similar observations have been put forward for the corresponding CI subunit [39].…”
Section: Discussionsupporting
confidence: 68%
“…Based on earlier reactivation experiments with oligomeric enzymes [34-361 it has been shown recently that E. coli tryptophan synthase f l~ subunit can be reversibly denatured in the presence of 2 4 M urea [37] or 4.5 M guanidine . HCl at acidic pH [38]. Similar observations have been put forward for the corresponding CI subunit [39].…”
Section: Discussionsupporting
confidence: 68%
“…Thus, the experimental value ~2 0 ,~~1 . 5 = 1.9 S found here compares well with the s20,w values reported for P chains in 0.1 M glycine/HCl, pH 2.3, plus 4.5 M GdmHC1 and in 4 M Gdn.HC1, respectively 1.7 S (Groha et al, 1978) and 2 S (C. R. Zetina and M. E. Goldberg, unpublished results),…”
Section: Methodsmentioning
confidence: 91%
“…The renaturation yield (in%) is shown as a function of the NDSB concentration and was determined as the ratio of the activity of the renatured sample to its theoretical initial activity, obtained from the specific activity of the native enzyme and the total protein concentration (0.5 mg/ml) in the renaturation buffer. previously been observed that Gdn/HCl unfolded β chains can fold efficiently only at low temperatures and low protein concentrations [19]. Unfolded β chains aggregate heavily and renature with extremely low yields (5Ϫ7 %) when folding is achieved at 0.5 mg/ml and 20°C.…”
Section: Resultsmentioning
confidence: 99%